Penerapan Relaksasi Spirotif pada Lansia dalam Upaya Pencegahan Kecemasan di Posyandu Lansia Dusun Ngemplak Kediri - Zulvana, Zulvana; Yektiningsih, Erwin; Yuliansari, Pratiwi (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2024)
Background: Promotive and preventive efforts are important factors as an effort to reduce morbidity in the elderly. One form of promotive and preventive effort to manage anxiety in the elderly can be done with physical and spiritual activities, namely spiritual relaxation. Objective: As an effort to increase the knowledge and skills of elderly people in preventing anxiety. Method: The method used is providing counseling and demonstration of Spiritual Relaxation. Results: It was found that 80% of participants were able to know the purpose of doing Spirotive Relaxation, 70% of participants were able to know the indications and contraindications of Spirotive Relaxation, and 75% of participants were able to know how to do Spirotive Relaxation. Conclusion: Based on the results, it can be concluded that there has been an increase in the knowledge and abilities of elderly people regarding spiritual relaxation as an effort to prevent anxiety. With counseling and demonstrations of Spirotive Relaxation, it is hoped that seniors can independently prevent anxiety.